Age-Dependent Prevalence of Loa loa Infection: Microfilaremia and IgG4 as Diagnostic Markers - Akue, J. P. (Disease and Health: Research Developments Vol. 5, 2025)
Background: Loiasis is caused by the human filarial Loa loa which is endemic in the west and Central African forest block. Loiasis infection is marked by long-term stability in infection status. The bases of such stability are not well known. As a preliminary step toward verification of possible genetic involvement in this stability. Methods: A survey in a homogeneous population (n = 106) of a village from an endemic zone of Gabon was undertaken. Microfilaremia under the microscope was examined, and anti–specific human IgG4 against adult worm Loa loa was measured. Results: The distribution of Loa loa microfilaremia according to age revealed a significant relationship between age and the presence of microfilariae in the blood (p = 0.0059). The proportion of microfilaremic individuals increased with age until 45 years old and did not exceed 34% as its maximum. The other marker (specific IgG4) increased also significantly with age (p = 0.0038), but in contrast to microfilaremia, the prevalence of specific IgG4, a marker of chronic infection, in the group from 45 years onward reached 100%. Conclusion: These findings highlight the role of age in defining amicrofilaremic or microfilaremic status in an endemic area and address the issue of the existence of genetic factors controlling the outcome of the parasitological status in L. loa infection.